A gender-sensitized weight management programme; an examination of the factors contributing to adherence with the rufit intervention - Norsyazmi Mohd
Introduction: The outcomes of poor dietary behaviour, sedentary-lifestyle and declining levels of physical activity in adult men can be seen with an increased prevalence of overweight and obesity, heart diseases, type-2 diabetes and other chronic diseases. Little work has been done to evaluate moderators and mediators of weight loss, in particular of adult men. Such explanation can provide better understanding of how, why, and when intervention work or will not work and who respond best to the treatment.Objectives: To examine the moderating and mediating variables contributing to adherence with the Rugby Fans in Training (RUFIT) intervention in promoting weight loss.Methods: The RuFIT programme was a randomised controlled trial with 83 overweight/obese men [(mean age = 42.7 ± 9.1; Body Mass Index (BMI) = 36.1 ± 7.1 kg/m)] randomised tp intervention group (n=45) and control group (n=38) for the 12 week study period. The primary outcome was change in the BMI. For physical fitness, it was assessed by recording the time to complete the 4-km Watt-bike test. By using a validated questionnaire, physical activity and dietry intake were measured. Moderating and mediating variables were evaluated by using multiple linear regression model. Results: At 12-week, the intervention group had a greater BMI reduction (-0.9 ± 2.3 kg/m). A linear regression model adjusting for baseline BMI shows that change in BMI in the intervention group was not significantly different from the control group (p=0.10; regression coefficient=0.30, 95% CI=-0.06 to 0.66). None of the hypothesised moderators and mediators mediated weight loss in the RuFIT programme. A small intervention effect (non-significant) favouring Maori/ Pacific, older participants (aged 51 years and above), and greater BMI at baseline were detected. Conclusion: Studies on moderators and moderators and mediators of weight loss, in particular to adult men in obesity treatment interventions is still lacking. All hypothesised variables fail to satisfy the criteria for moderation and mediation in the current study. These finding can serve as a reference data for the continuity of future obesity treatment and as prevention programmes among overweight or obese adult men.